Analisa Pengukuran Ketebalan Steel Block, Aluminium Block dan Steel Plate Menggunakan Ultrasonic Thickness Gauge - Unggul Satria Jati; Radhi Ariawan; Dian Prabowo; Sabtun Ismi Khasanah; Hamid Abdillah; Ulikaryani, Ulikaryani (P3M Politeknik Negeri Cilacap, 2025)
Thickness measurement using an ultrasonic sensor is a type of non-destructive test (NDT) that is commonly used in various industries. Measurement of thickness (thickness) on steel blocks, aluminum blocks and steel plates using an ultrasonic thickness gauge. The method used is the contact testing method which is then compared with manual measurements. Based on data analysis from the measurement results, it was found that the thickness with the highest percent error was in the Steel S3 sample, namely 93.87%. Meanwhile, the thickness measurement with the lowest percent error in the Steel plate sample was 0%. Meanwhile, for measuring the dimensions of artificial corrosion defects, the smallest error percentage obtained was 0% for several dimensions, with the average measurement error obtained being 22.82%. The profile shape of the detected artificial corrosion defects is exactly the same as the reference profile. So, measuring the thickness of steel blocks, aluminum blocks and steel plates as well as measuring artificial corrosion defects located in steel plates can be detected well and the measuring results can be trusted.